Disappearing Acts, or the Absent Character in the Plays of Elena Garro - Messinger Cypess, Sandra (Latin American Theatre Review, 2016)
Walter Benjamin’s ideas concerning the incommunicability of experiences suggest that there are events for which those involved cannot find listeners capable of comprehending their experiences. When such moments of incommunicability occur in Elena Garro’s dramatic world, many of her characters simply disappear from the scene. This article examines the dramatic function of disappearance in four of Garro’s plays, illustrating that there is no one way for characters to withdraw. El Encanto, Tendajón mixto, for example, depicts the rare occasion in which a character is fortunate enough to find a companion who leads him to a more amenable existence, while others, like Titina in Andarse por las ramas, absent themselves by choice. In all of the plays examined, Garro imparts her vision of how incommunicability affects interactions and often harms individuals.